Narrative Text to Encourage Students Skill in Speaking - Duendi Sata, Nashih Rojabi; Desy Wardani, Ika; Sabartono, Ribut (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2023)
This research delves into the exploration of enhancing English as a Foreign Language (EFL) students' confidence in speaking through the use of narrative text, specifically employing the movie